The definitive guide to CentOS - Membrey, Peter; Verhoeven, Tim.; Angenendt, Ralph (Berkeley, CA : Apress, 2009)
Provides information on network administration using CentOS.
Includes index.
Keywords: Linux; Linux (Computer software); Operating systems (Computers); Computer operating systems